IMPACT OF GOVERNMENT PUBLIC EXPENDITURE ON POVERTY LEVEL IN SOUTH SULAWESI PROVINCE - Sapriyadi Sapriyadi (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
Poverty is always a problem in the development of a country, especially in the economic field. Poverty from the economic side has an impact on the decline in people's purchasing power, while in the social aspect, poverty is seen as a problem when social stratification in society creates a dividing line where the upper class does not want to interact with the lower class society and vice versa. This study aims to determine the impact of government public spending on education and health functions on the level of poverty. The scope of the research covers 24 districts/cities in South Sulawesi Province from 2015-2019. The type of research used is quantitative, using secondary data. The data collection method was carried out through online searches on the official websites of DJPK and BPS. The data analysis technique used is path analysis. The results show that education spending directly has a positive impact on poverty levels, and health spending has a negative impact on poverty levels. Meanwhile, education spending indirectly has a negative impact on poverty levels through Gross Regional Domestic Product, and health spending has a positive impact on poverty levels through Gross Regional Domestic Product.